INTERACTIVE METHODS OF LEARNING RUSSIAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Methods of teaching the Russian language (MPRY) - the science of the goals, content, principles and methods of teaching the Russian literary language, ways and conditions of students' acquisition of knowledge and development of Russian language skills in primary school. MNR as a science answers the following questions: What should be taught? As an answer to this question, it is possible to cite the content of education - the development of educational programs in the Russian language, the creation of textbooks and study guides for students, their continuous improvement, and checking their usability and effectiveness.